Rational solitons for non-local Hirota equations: Robustness and cascading instability - Pan, Q.; Yin, H. M.; Chow, K. W. (Frontiers in Physics, 2023)
The Hirota equation is a higher-order nonlinear Schrödinger equation by incorporating third-order dispersion. Two pairs of nonlocal Hirota equations are studied. One is a parity transformed conjugate pair, and the other is a conjugate PT-symmetric pair. For the first pair, rational solitons are derived by the Darboux transformation, and are shown computationally to exhibit robust propagation properties. These rational solitons can exhibit both elastic and inelastic interactions. One particular case of an elastic collision between dark and ‘anti-dark’ solitons is demonstrated. For the second pair, a ‘cascading mechanism’ illustrating the growth of higher-order sidebands is elucidated explicitly for these nonlocal, conjugate PT-symmetric equations. These mechanisms provide a theoretical confirmation of the initial amplification phase of the growth-and-decay cycles of breathers. Such repeated patterns will serve as a manifestation of the classical Fermi-Pasta-Ulam-Tsingou recurrence.